Cost optimisation of supply chain networks using particle swarm optimisation. (26th October 2010) - Shankhar, C.; Prasad, P.S.S.
Product cost is one of the key parameters in sustaining the competitiveness of the organisations. Though several cost elements are contributing towards total cost of the product, transportation costs are becoming dominant due to increasing outsourcing activities. There may be considerable scope to reduce these costs by effective supply chain modelling. In this context this paper considers two level distribution network involving location of warehouses and assigning distribution centres (DCs) to appropriate warehouse and made an attempt to identify the minimum cost distribution planning by way of clustering the DCs. In order to arrive at optimal distribution network, particle swarm optimisation (PSO) technique is proposed and results indicate the effectiveness of the proposed methodology.